Wavelength Conversion Scheme for Dedicated Protection in WDM Optical Networks - Suthaharan, S.; Ravithas, N.; Sharfana, F.A. (IEEE International Conference on Industrial and Information Systems (ICIIS), 2017)
Optical communication is the emerging technology for data transmission systems because of their large information-carrying capacity. Wavelength division multiplexing (WDM) in optical networks is a method to deal the Internet traffic more effectively. Various divided channels are used in WDM to enable data transmission on a fiber. Failure of the optical fiber causes loss of huge amount of data which can interrupt communication. To protect such failure, we consider dedicated protection in this paper in which backup paths are configured at the time of establishing connections. If a primary path is failed, the traffic is rerouted through secondary path with a short recovery time. Further, non-wavelength conversion is a wavelength assignment scheme which incorporates with wavelength continuity constraint method. Therefore, the blocking of connections can be increased. To reduce the blocking, we focus a scheme known as wavelength conversion technique in this paper which leads to the less blocking of the connections. In this paper, we carry out the investigation with detailed simulation experiments on different data rates scenarios. In addition, this paper focuses on three standard network topologies which consist of different number of links to identify how the blocking performance varies for each network. Our findings are as follows. (1) The considerable reductions have been achieved in each of the network loads in a particular network topology. (2) The blocking performance for network topology with low number of links and network topology with high number of links are comparable.
Keywords: optical networks; dedicated protection; wavelength conversion